Study protocol for “psilocybin as a treatment for anorexia nervosa: a pilot study” - Spriggs, MJ; Douglass, HM; Park, RJ; Read, T; Danby, JL; de Magalhães, FJC; Alderton, KL; Williams, TM; Blemings, A; Lafrance, A; Nicholls, DE; Erritzoe, D; et al. (Frontiers Media, 2021)
Background: Anorexia nervosa (AN) is a serious and life-threatening psychiatric condition. With a paucity of approved treatments, there is a desperate need for novel treatment avenues to be explored. Here, we present (1) an overview of the ways through which Public Patient Involvement (PPI) has informed a trial of psilocybin-assisted therapy for AN and (2) a protocol for a pilot study of psilocybin-assisted therapy in AN currently underway at Imperial College London. The study aims to assess the feasibility, brain mechanisms and preliminary outcomes of treating anorexia nervosa with psilocybin.